PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKANMETODE DIVISI PRESTASI SISWA DALAM KELOMPOK SISWA KELAS VIIIMTs NEGERI PAKEM SLEMAN YOGYAKARTA - Dewi Astuti, . (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
Reading activity is a very important activity in an academic society because most of knowledge canbe obtained by reading. People know many things fast and in a modern way by reading so that they arenot left behind. The method of Student Achievement Division in group of the cooperative learningmotivates students to help one another, to motivate, and to master skills given by the teacher.This research used Classroom Action Research and the research subjects were the students of gradeVIII C of MTs Negeri Pakem Sleman Yogyakarta.The result of the research shows that the use of the Student Achievement Division Method in groupin the reading comprehension instruction can increase the students’ reading comprehension ability. Theaverage score that could be reached by the students in the last action of Cycle I was 88. The increasingscore from the last action of Cycle I and the last action of Cycle II were 4.25 or 5.07%. It can be seen fromthe average score of 83.75 which became 88. In addition, to increase the reading comprehension ability,the Method of Student Achievement Division in groups could increase students’ motivation in the readingcomprehension instruction. It can be seen that the students could be more active, enjoy the learningprocess, and respond to the reading comprehension activity.Keywords: reading comprehension, Student Achievement Division Method